2019
DOI: 10.3389/fpls.2019.00941
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Networks for the Automatic Identification of Plant Diseases

Abstract: Deep learning techniques, and in particular Convolutional Neural Networks (CNNs), have led to significant progress in image processing. Since 2016, many applications for the automatic identification of crop diseases have been developed. These applications could serve as a basis for the development of expertise assistance or automatic screening tools. Such tools could contribute to more sustainable agricultural practices and greater food production security. To assess the potential of these networks for such ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(141 citation statements)
references
References 46 publications
0
121
0
4
Order By: Relevance
“…Of the six models, NASNetLarge performed the best with 54 misjudgments (Figure 2), and among them, Nannong 1606 had the most misjudgments while Shangdou 1201 and Zheng 3074 had the least misjudgments. According to the study, the greater the number of deep neural network layers, the better the performance of the identification models, and the conclusion is the same in other fields [49][50][51]. However, there are also different conclusions [46,[52][53][54], as there are several factors that cause this situation, including dataset, network depth, network width, network structure, and parameter settings, and overall, the deep network is indeed slightly better than the shallow network.…”
Section: Test Resultsmentioning
confidence: 91%
“…Of the six models, NASNetLarge performed the best with 54 misjudgments (Figure 2), and among them, Nannong 1606 had the most misjudgments while Shangdou 1201 and Zheng 3074 had the least misjudgments. According to the study, the greater the number of deep neural network layers, the better the performance of the identification models, and the conclusion is the same in other fields [49][50][51]. However, there are also different conclusions [46,[52][53][54], as there are several factors that cause this situation, including dataset, network depth, network width, network structure, and parameter settings, and overall, the deep network is indeed slightly better than the shallow network.…”
Section: Test Resultsmentioning
confidence: 91%
“…Visualisation techniques observe whether the classifier has selected all the areas of disease in the given image without being affected by the background or noise. In [ 35 , 88 ], the occlusion technique was shown to have an issue in identifying whether a pixel represented symptoms of the right class or part of the background. Additionally, in [ 80 ], it was found that the occlusion technique was time-consuming.…”
Section: Feature Representation In Deep Classifiersmentioning
confidence: 99%
“…The identification process in classifiers is based on how ROIs are localised. Many techniques have been discussed in relation to this issue, including segmentation, object detection and hybrid methods that supply classifiers with contextual information related to the ROI and thereby affect their performance [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In [15], Boulent et al use three types of data sets depending on their complexity in the automatic identification of plant diseases: The first image samples are captured under controlled situations where the leaves are placed on the same background and brightness. The second image samples are taken under unrestrained conditions and focus is made on specific plant organ.…”
Section: Review Of Related Workmentioning
confidence: 99%